Silver Nanoparticles Impregnated Mesoporous SBA-15 - Batish, Sandeep (My University, 2012)
Silver impregnated SBA-15 has been prepared by one- and two- pot synthesis. In one pot synthesis three different reducing agents viz., hexamine, ascorbic acid and ammonia were used for preparation of Ag incorporated SBA-15 and as prepared catalysts were named as Ag/SBA-15/Hex, Ag/SBA-15/Asc, and Ag/SBA-15/NH3. However, in two pot synthesis, seed solution of Ag nanoparticles were introduced at two different stages during synthesis of SBA-15 and were abbreviated as Ag/NP-1/SBA-15 and Ag/NP-2/SBA-15. The synthesized samples were characterized by powder X-ray diffraction, BET surface area, SEM and EDX analysis. The surface areas of prepared catalysts were found to be 439 m2/g (Ag/SBA-15/NH3), 485 m2/g (Ag/SBA-15/Asc), 510 m2/g (Ag/SBA-15/Hex), 607 m2/g (Ag/NP-2/SBA-15) and 626 m2/g (Ag/NP-1). These values are lower than that of SBA-15 (702 m2/g), suggesting the incorporation of Ag into SBA-15. All the prepared catalysts were tested for oxidation of cyclohexane to cyclohexanone. The highest conversion of 2.5% was obtained with Ag/SBA-15/Hex, whereas other catalysts showed 1.6-2.2% conversion. Hence, Ag/SBA-15/Hex was used for further oxidation of three cycloalkanols viz., cyclopentanol, cyclohexanol and cycloheptanol that resulted in 55%, 38.7%, 33.7% conversion, respectively into their respective cycloalkanones.
M.Sc. (Chemistry)
Keywords: Silver nano particles; SBA 15